Shift in the Use of River Transportation to Land Transportation in Banjarmasin City 2000-2020 - Bachtiar Bachtiar; Bambang Subiyakto; Melisa Prawitasari (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The river transportation in Banjarmasin City is experiencing a shift where people prefer to use land transportation over river transportation. This is happening due to several driving factors causing the community to abandon river transportation. As Banjarmasin City is dubbed as the city of a thousand rivers, this contrasts with the abandonment of river transportation. This writing aims to understand the reasons behind the shift from river transportation to land transportation for the people of Banjarmasin City. The method employed in this research is historical methodology, which involves four stages: heuristic, comprising the collection of historical sources such as data, source criticism, interpretation, and historiography. The research findings indicate several causes for the decline in river transportation usage, leading the community to shift to land transportation. These include river narrowing, construction of excessively low bridges, and accumulation of waste on the river surface, which hinder the speed of river transportation flow.